Effectiveness Test of Granulated Bioinsecticide Formulation from Avocado Seed Extract Against Aedes aegypti Larvae - Amir, Rahmi; Amrin; Bastiana; Tatiana; Fitriana; Nirwana; Syarief , Faisal (Public Health of Indonesia, 2025)
Background:Vector-borne diseases, notably Dengue Hemorrhagic Fever (DHF), represent a significant global health challenge, with the World Health Organization (WHO) estimating approximately 390 million infections annually. The Aedes aegypti mosquito, the primary vector of DHF, has developed resistance to conventional chemical insecticides, necessitating the exploration of eco-friendly alternatives. Avocado seed (Persea americana) extract, rich in insecticidal compounds such as flavonoids, tannins, and saponins, presents a promising source for bioinsecticides. Granulated formulations offer advantages over liquid formulations, including enhanced stability, controlled release, and greater practicality in field applications. Objectives:This study aims to investigate the sustainable application of health management information systems and the role of health information technology strategies in supporting the continued use of such systems. Specifically, the focus is on the implementation of granulated bioinsecticide formulations derived from avocado seed extract as a sustainable solution for controlling Aedes aegypti larvae. Methods:An experimental laboratory study was conducted at the Phytochemical Pharmacy Laboratory, ITKES Muhammadiyah Sidrap, in September 2024. Granulated bioinsecticides were prepared from avocado seed extract and evaluated for their efficacy in controlling Aedes aegypti larvae. A total of 25 third-instar larvae were included in both experimental and control groups, with concentrations of 10, 15, 20, and 25 ppm administered. Larval mortality was assessed at 24 and 48-hour intervals. Statistical analysis was performed using ANOVA, followed by post-hoc tests to determine significant differences. Results:The granulated bioinsecticide demonstrated a high level of efficacy, achieving a mortality rate of 94.2% at 25 ppm within 72 hours, compared to 58.5% at 10 ppm. ANOVA results indicated that both the concentration of the bioinsecticide and the exposure duration significantly affected larval mortality (p < 0.05). The granulated formulations exhibited prolonged effectiveness and a controlled release of active compounds, supporting their potential for large-scale applications. Conclusion:The granulated bioinsecticide formulated from avocado seed extract offers an eco-friendly and effective alternative for controlling Aedes aegypti larvae. The findings highlight its stability and scalability for use in vector control programs, contributing to sustainable public health initiatives. Further research should focus on optimizing the formulation, conducting field trials, and evaluating potential environmental impacts to maximize its practical applicability.  Keywords:avocado seed; Bioinsecticide; Aedes aegypti; Granules; Dengue vector control